CAMPURAN KOMPOS TANDAN KOSONG KELAPA SAWIT DENGAN KOMPOS LCC DAN PUPUK FOSFOR TERHADAP PERTUMBUHAN DAN HASIL SORGUM (Sorghum bicolor (L.)) - Yulia Handayani; Jurnawaty Sjofjan; Husna Yetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research is aimed to determine the effect of oil palm empty fruit bunches compost mixed with leguminosa cover crop compost and phosphorus fertilizers at some compositions and to get the best mixed toward growth and result of sorghum. This research was conducted at the experiment land of Agriculture Faculty of Riau University, Pekanbaru, from December 2013 to April 2014. This research used factorial completely randomized design (CRD) consisted of two factors and three replications. As for the treatment is: factor 1 is oil palm empty fruit bunches compost mixed with leguminosa cover crop compost (K) consist of four level, K1= 5 ton/ha oil palm empty fruit bunches compost, K2= 3,75 ton/ha oil palm empty fruit bunches compost + 1,25 ton/ha leguminosa cover crop compost, K3= 2,5 ton/ha oil palm empty fruit bunches compost + 2,5 ton/ha leguminosa cover crop compost, K4= 1,25 ton/ha oil palm empty fruit bunches compost + 3,75 ton/ha leguminosa cover crop compost. Factor 2 is phosphorus fertilizers (P) consist of three level, P0= without TSP, P1= 30 kg/ha TSP, P2= 60 kg/ha TSP. The results of this research showed that 1,25 ton/ha oil palm empty fruit bunches compost mixed with 3,75 ton/ha leguminosa cover crop compost and 60 kg/ha phosphorus fertilizers provide the best results for 245,20 g/m2(2,45 ton/ha) increased by 18,27% compared without P and is significant for the parameters of plant height, dry weight of plants, result per m2 and sorghum biomass. Keywords: oil palm empty fruit bunches compost, leguminosa cover crop compost, phosphorus fertilizers, Sorghum bicolor L.